Detecting Driver Yawning in Successive Images - Lu, Yufeng; Wang, Zengcai (2007 1st International Conference on Bioinformatics and Biomedical Engineering, 2007)
We can detect drivers' yawn to recognize the drivers' state in the process of drivers' state detection. The face region is located using the difference image between two images. The face region is segmented and the chin is located, then the midpoint of nostrils is located using directional integral projection method. Based on the locating of the midpoint of nostrils and the chin we can recognize the drivers' yawn by calculating the vertical distance between them. Our method is robust to variant illumination because this method isn't based on color or intensity which is fragile to illumination. The experiments results that the method we present can detect most yawning in test videos.